2020
DOI: 10.3389/fmars.2020.00138
|View full text |Cite
|
Sign up to set email alerts
|

Complex Dispersal of Adult Yellowfin Tuna From the Main Hawaiian Islands

Abstract: Local availability of yellowfin tuna, Thunnus albacares, is a key economic, dietary and cultural concern for Main Hawaiian Islands (MHI) communities and insular fisheries. Consequently, interactions of inshore vs. offshore fisheries and connectivity to yellowfin elsewhere in the Pacific remain important scientific management questions. Local fisheries target adult tuna during the summer months, but subsequent tuna movements, presumably away from the islands after reproduction ceases, remain undocumented. From … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 40 publications
1
9
0
Order By: Relevance
“…Tag failure, as reported in this study and others (e.g. Lam et al, 2020), has increasingly become a costly impediment to our ability to track and observe billfish and tuna (Musyl et al, 2011;Lutcavage et al, 2015). To ensure the least amount of bias introduced into stock assessment and fisheries management, stakeholders must encourage tag manufacturers to provide reliable products with consistent performance, and push for innovation in tracking technologies so that research dollars can be spent most effectively.…”
Section: Mixing Gene Flow and Management Considerationssupporting
confidence: 67%
“…Tag failure, as reported in this study and others (e.g. Lam et al, 2020), has increasingly become a costly impediment to our ability to track and observe billfish and tuna (Musyl et al, 2011;Lutcavage et al, 2015). To ensure the least amount of bias introduced into stock assessment and fisheries management, stakeholders must encourage tag manufacturers to provide reliable products with consistent performance, and push for innovation in tracking technologies so that research dollars can be spent most effectively.…”
Section: Mixing Gene Flow and Management Considerationssupporting
confidence: 67%
“…Other studies of tagged tuna captured by rod and reel also indicate that tagging itself does not result in high levels of mortality (e.g. Lam et al 2020Tolotti et al 2020, and lab studies also showed no survival or behavioural impacts of satellite tagged, captive mahimahi (Coryphaena hippurus) compared to untagged conspecifics (McGuigan et al 2021). It appears that the commercial longline hauling is more responsible for the high mortality we have observed, rather than the satellite tagging procedure itself.…”
Section: Discussionmentioning
confidence: 94%
“…Additionally, 57% of tags deployed in this study did not report. Having more than half of the total number of purchased tags as non-reporting was not only financially expensive but also resulted in significant loss of scientific opportunity, as has repeatedly been reported in PSAT studies e.g., [ 11 , 41 , 42 ]. In terms of seasonal analysis, it prevented us from attaining equal numbers of tracks per month, which would have been necessary to fully characterise seasonal patterns.…”
Section: Discussionmentioning
confidence: 99%